Principles of the compliance program of industrial enterprise - Kobielieva, T. O.; Mygushchenko, R.; Tkachova, N. P. (Miskolci Egyetem Gazdaságtudományi Kar, 2017)
Occupying a leading position in the industry, the enterprise should be aware of its high responsibility for transparency, ethics and the legitimacy of doing business. In order to maintain and maintain its high business reputation to the state, shareholders, customers, partners, competitors and the society as a whole, the company throughout its operations must actively develop a corporate system to ensure compliance with applicable laws and ethical business conduct ("compliance"). To achieve this goal, the enterprise must be guided by certain principles. The basic principles of compliance are determined by the Basel Committee on Banking Supervision in the document "Compliance and Compliance Function in Banks". This document was issued by this committee in April 2005. In spite of the fact that initially the Basel Committee defined compliance principles for the banking sector of the economy, at the present time they basically approach the activities of any enterprise or institution. At the same time, as the results of our studies show, there are certain differences in the structures and content of compliance principles, which depend on the scope of application of the program's compliance (banks, institutions, industrial enterprises, etc.).
Keywords: compliance; competitive; service; industrial enterprises